Effects of mulching and zinc on physiological responses and yield of sweet pepper (Capsicum annuum) under high altitude cold desert condition - SINGH, RAJENDRA KUMAR; ACHARYA, SOMEN; CHAURASIA, O P (The Indian Journal of Agricultural Sciences, 2019)
In arid regions of the world, drought stress, lack of water availability and micro nutrient deficient sandy soils affect normal growth and development of plants resulted in poor growth and yield. The aim of the study was to evaluate combined effects of mulching and zinc application on growth, physiological responses and yield of capsicum (Capsicum annuum L.) under high altitude cold desert conditions. Field experiment was conducted in the cold desert environment of trans-Himalayan Ladakh region with five levels of zinc (ZnSO4), viz. 0, 10, 20, 30 and 40 kg ha-1 with and without polythene mulching during 2013 and 2014 cropping season. Results showed that mulching with zinc significantly improved leaves membrane stability index (MSI) and relative water content (RWC) and also helped in reducing leaf water loss (LWL) and electrolyte leakage (EL) indicating better plant physiological responses. Significant improvement in leaf chlorophyll content was also observed. Both mulching and zinc application remarkably enhanced plant growth characters and capsicum yield. But, during 2014, sudden decrease in minimum and maximum temperature at flowering and fruiting stage adversely affected proper fruit set and its development resulting into poor capsicum yield. Application of mulch also reduced irrigation water requirement of plants. Knowledge from the present study indicated that combined application of ZnSO4 and mulching could be the feasible strategy against weather abnormality, water savings and obtaining better yield of vegetables grown in zinc deficient sandy soils of arid regions.